Determinants Of Income Smoothing: The Role Of Leverage, Firm Value, and Cash Holding - Nurlaela (Universitas Serang Raya, 2025)
Income smoothing is an accounting practice used by companies to reduce earnings fluctuations, enhance financial statement stability, and increase investor confidence. This study examines the impact of Cash Holding, Price to Book Value (PBV), and Debt to Equity Ratio (DER) on Income Smoothing in the Properties and Real Estate sector listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. The population consists of all Properties and Real Estate companies listed on the IDX, with a purposive sampling technique yielding a final sample of 105 companies. Using the Generalized Method of Moments (GMM) approach, this study addresses issues of endogeneity and individual heterogeneity in financial analysis. The partial t-test results indicate that DER has a positive and significant effect on Income Smoothing, while Cash Holding and PBV do not have a significant impact. The simultaneous F-test results confirm that the three variables collectively influence Income Smoothing significantly. Model validation using the Hansen-J Test and AR(2) Test ensures that the GMM estimations are valid and free from serial correlation issues. The Adjusted R² of 0.225 suggests that the model explains 22.5% of the variation in Income Smoothing. Furthermore, Robustness Test & Machine Learning Validation using Quantile Regression, Bayesian Model Averaging (BMA), XGBoost, and Random Forest reinforces that DER is the primary factor influencing Income Smoothing. These findings highlight the critical role of leverage in corporate managerial practices, emphasizing its importance for investors and regulators when assessing financial statements in the real estate sector.